Pengolahan Air Sadah Menggunakan Zeolit Buatan Dari Batu Apung Lampung Dan Daun Kerai Payung - Nindia Agustin; Pulung Karo Karo; Sudibyo Sudibyo; Suprihatin Suprihatin (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
This research was conducted to determine the composition and crystal structure of the artificial zeolite produced, as well as the ability of artificial zeolite to reduce calcium and magnesium content in hard water. The zeolite was prepared using the hydrothermal method by mixing sodium silicate from Lampung pumice silica, sodium aluminate from aluminum can waste and charcoal from sunshade umbrellas. The artificial zeolite products were characterized using XRF, XRD, UV-Vis spectrophotometric and ICP-EOS. The results showed that the composition of the artificial zeolite was aluminum, silica, phosphorus, potassium, calcium, titanium, vanadium, chromium, manganum and ferum. The crystal structure of the optimum sample from the UV-Vis spectrophotometric characterization obtained the crystal structure of a natural zeolite type, namely Chabazite. And the artificial zeolite which was tested for adsorption on hard water could reduce the calcium content by 36.57% but could not reduce the magnesium content.